Analysis of the Implementation of Management Work Lectures (KKM) in Improving Students' Professional Competence at the Medan Amplas District Office - Arief Hardian; Syabila Syazwana; Gladis Pradani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of the Management Internship Program (KKM) and its contribution to improving students' professional competence at the Medan Amplas District Office. The background of this study stems from the need for higher education to produce graduates who not only master theory but also possess practical skills appropriate to the demands of the workplace, particularly in government administrative environments. This study used a qualitative descriptive method through in-depth interviews, questionnaires, and direct observation of KKM participants and field supervisors. The results showed that the KKM program had a significant impact on improving students' professional competence. Improvements were seen in hard skills, such as understanding of government administration (88%), ability to use office applications (81%), and report preparation (76%). In addition, there was a significant increase in soft skills, including communication skills (92%), discipline (85%), and self-confidence in completing tasks (78%). Direct interaction with employees and the community and active guidance from field supervisors were key supporting factors in the program's effectiveness. However, the study also identified several obstacles such as limited supervision and high agency workload. Overall, this study concludes that KKM plays an important role as a contextual learning tool that is able to improve students' professional competence through the application of theory to real practice in the government environment.